2021
DOI: 10.1111/jfbc.13935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donkey milk on oxidative stress and inflammatory response

Abstract: Donkey milk is gaining interest as a natural nutritional and medicinal product, mainly because its composition is similar to that of human milk, and it has some potential biological properties, such as antioxidant, anti-inflammatory, antiaging, antimicrobial, and anticancer properties. Considering the increasing prevalence of several chronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 107 publications
0
11
0
2
Order By: Relevance
“…Additionally, Donkey milk inhibits gluconeogenesis by regulating the expression levels of phosphoenolpyruvate carboxykinase 1 and glucose-6 phosphatase. Donkey milk enhances the antioxidant defense mechanisms by which it protects the development of insulin resistance 38 . Lactose, whey protein and bioactive peptides in DM have been shown to be involved in insulin response to glucose.…”
Section: Donkey Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Donkey milk inhibits gluconeogenesis by regulating the expression levels of phosphoenolpyruvate carboxykinase 1 and glucose-6 phosphatase. Donkey milk enhances the antioxidant defense mechanisms by which it protects the development of insulin resistance 38 . Lactose, whey protein and bioactive peptides in DM have been shown to be involved in insulin response to glucose.…”
Section: Donkey Milkmentioning
confidence: 99%
“…Camel milk is well known for its anti-diabetic, anti-carcinogenic, immunomodulatory, and anti-microbial effect 65 . Donkey milk is gaining attention as a natural nutritional and medicinal product, mainly because its composition is parallel to that of human milk and it has some potential biological properties, such as antioxidant, antiinflammatory, antiaging, antimicrobial, and antiallergic 38 .…”
mentioning
confidence: 99%
“…Donkey milk is enriched with bioactive and anti-infective factors and is characterized by its palatability, digestibility, and hypoallergenicity. Owing to these qualities, donkey milk can be used as an effective alternative food for neonates, and owing to its broad-spectrum functional activities (which include anti-inflammatory, antioxidant, and antiaging activities), a medicinal and food homology that meets the nutritional needs of people in different physiological states . Notably, donkey milk has a smaller volume of milk fat globule (MFG) than human milk, with an average diameter of 1.50 μm compared to 5.19 μm for human MFG .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these qualities, donkey milk can be used as an effective alternative food for neonates, and owing to its broad-spectrum functional activities (which include antiinflammatory, antioxidant, and antiaging activities), a medicinal and food homology that meets the nutritional needs of people in different physiological states. 1 Notably, donkey milk has a smaller volume of milk fat globule (MFG) than human milk, with an average diameter of 1.50 μm compared to 5.19 μm for human MFG. 2 A smaller MFG diameter per unit volume implies a larger specific surface area of the milk fat globule membrane (MFGM), which may contribute to the interaction between host enzymes and the functionally active components of the MFGM, promoting the higher digestion and absorption rate of donkey MFGM in the body.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional use of donkey milk for the treatment of many illnesses has been reported in China, South America, and some African societies Fantuz, 2013, 2022;Papademas et al, 2022). In recent years, the donkey has gained interest as a species producing dairy foods for consumers sensitive to cow milk, such as infants, adults with inflammatory or allergic ailments, and healthy older people (Miraglia et al, 2020;Li et al, 2021;Papademas et al, 2022;Salimei and Fantuz, 2022). Clinical studies have shown that donkey milk can be used, when adequately supplemented, for children with IgE-and non-IgE-mediated cow milk allergy (Mansueto et al, 2013;Salimei and Fantuz, 2013;Sarti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%